Can we stop the stroke tsunami? Mitigating the barriers, amplifying the facilitators. Issue 2 (15th March 2022) - Krishnamurthi, Rita; George, Ann; Merkin, Alexander; Bhattacharjee, Rohit; Feigin, Valery L.
ABSTRACT: In this narrative review article, by critically appraising the Global Burden of Disease 1990–2017 data on stroke and currently used primary stroke prevention strategies, we show that the global burden of stroke will continue to rise unless new primary stroke and cardiovascular disease (CVD) prevention strategies are urgently implemented. We provide an overview of the advantages and disadvantagesof population-wide and high CVD risk prevention strategies and mobile technologies available for stroke and CVD prevention on individual and population levels. Our recent NZ pilot RCT demonstrated the feasibility, consumer acceptability, motivational value and a clinically important, albeit statistically non-significant, behaviour change, improvement in diet, and awareness of stroke symptoms. We also identify and discuss causes for failure in the currently used primary stroke and CVD prevention strategies and emphasise the importance of complementary use of population-wide and elevated CVD risk strategies (including polypill interventions with blood pressure and lipid-lowering off-patent medications in middle-aged adults with elevated CVD risk) with motivational population-wide strategy to manage lifestyle and behavioural risk factors regardless of the level of stroke risk. The best mix of population-wide and elevated CVD risk-targeted strategiesfor primary stroke and CVD prevention remains to be determined.